Arabic language in Zanzibar: past, present, and future. (4th May 2018) - Gintsburg, Sarali
ABSTRACT: The debate on the status and the role of Standard/Classical Arabic versus Dialectal Arabic in the Arab World has a long history. In parallel to this, voices calling for giving Dialectal Arabic the status of the official state language and cancelling Standard Arabic altogether are becoming louder. This debate is being fuelled by the rapidly developing theory of superdiversity which claims that, due to the rapid changes that happened to the world after 1991, and increasing globalization associated with worldwide migration, easy access throughout the world to internet and social networks, video hosting services and satellite television, societies all over the world have become extremely diverse linguistically. This theory also draws on language ideologies, the concept that suggests that the traditional idea of a "language" is an ideological artefact. Is this approach valid for understanding what is happening in the Arabic language? I will attempt to answer this question by examining the status of the Arabic language on the margins of the Arab world – in Zanzibar. For centuries, the Arabic language has been one of the key languages spoken in Zanzibar, but it has now been practically replaced by Swahili.